ANALISIS REFERENSIAL DALAM MANTRA MASYARAKAT MELAYU SAMBAS DI KECAMATAN JAWAI - Wolly Capriati; Agus Syahrani; Henny Sanulita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractReference is a connection between words and things which is become references. Magical words is one of culture society. That magical words will be tell and expressed in order to reach the user wishes itself or others wishes. The objective of this research was to describe the specific problem that have been studied, meanwhile the benefit of this research is theorit ically can enrich vocabullary of language of local wisdom which generally is Sambas society and specifically is Jawai District Society and practically has benefit for researcher, readers, and educators. The method used in this research was descriptive, the research form is qualitative and discourse analysis approach. The data source in this research was Batra or magical words user and thedata is that magical words itself. Technique of data collecting in this research was elecitation, recording and writing tecnique. Based on the result of data analysis about referential analysis in magical words of Sambas Malay Society in Jawai District. Based on kind of marker, form of marker, proporion of kind and form of marker, and lesson implementation in the school which can be found in magical world that most used by people is the kind of marker persona with the marker form is ‗I‘ and (my—).Keywords: Batra, Magic, Reference.